(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The paper deals with the improved mining design method for Estonian oil shale mines, where the room-and-pillar mining system is used. Design of mining block parameters is based on the instruction used in Estonian oil shale mines. The factor of safety is very large. Consequently, the design method does not take into consideration all the influence factors. It is determined the supplementary influence factors and given the mathematical formulas. In this case the factor of safety is reduced up to 1.2. The improved mining design method is of particular interest for practical purposes.